Stacked Tantalum Cones as a Method for Treating Severe Distal Femoral Bone Deficiency in Total Knee Arthroplasty - Rajgopal, Ashok; Panda, Inayat; Yadav, Sidharth; Wakde, Om (The Journal of Knee Surgery, 2019)
Severe bone loss in distal femur has traditionally been managed with bulk cementing, bone graft, metal augments, trabecular metal cones, and mega prosthesis. The authors present an alternative method using a stacked configuration of two tantalum cones to manage severe distal femoral bone loss. This study aims to evaluate the mid-term outcomes and possible complications in patients treated with this novel technique. We retrospectively analyzed the prospectively maintained records of 16 knees (in 16 patients) presenting with severe distal femoral bone deficiency due to septic loosening (5), giant cell tumor (GCT; 4), periprosthetic fracture (3), aseptic loosening (3), and distal femoral comminuted fracture with severe osteoarthritis (1). A standard medial parapatellar approach was taken in all our cases followed by preparation of distal femoral bone defect and use of two bridging tantalum trabecular metal cones to fill the defect, followed by implantation of rotating hinge knee prosthesis. At an average follow-up of 57 months (4.75 years), the average Knee Society Score was 74.56 (64–87) and the mean range of motion was 97.8 (70–120) degrees. Radiologically, all 16 knees showed good osteointegration with no evidence of progressive radiolucency or loosening. Complications included two patients with superficial infection (healed with antibiotics), and one with recurrence of GCT requiring tumor megaprosthesis reconstruction. The authors concluded that the stacked configuration of cones provides additional coverage and stability with good osteointegration and found it to be particularly useful in distal femoral GCTs and fracture situations. They recommend the use of stacked cones in selected cases of severe distal femoral deficiency.
Keywords: stacked trabecular metal cones; tantalum cones; revision knee arthroplasty; distal femoral bone defect